A moving target: Universal access to healthcare services in Latin America and the Caribbean - William D. Savedoff (Inter-American Development Bank, Research Department, 2009)
Healthcare services are more widespread in Latin America and the Caribbean today than 50 years ago, yet this availability is not necessarily reflected in popular perceptions. This study documents the expansion of healthcare services in the Region in terms of medically-trained professionals, service utilization, and insurance eligibility. It finds that people in countries with more doctors have a more positive view of access to healthcare and greater confidence in the healthcare system. However, other factors intervene in this relationship between perceptions and objective indicators, such as the strength of local social networks and wealth. As a consequence of rising expectations, differential access and continuing discontent, public policy can be driven by factors that are least likely to improve the population's health.
Keywords: I18; I11; N96; 330; Health Care; Health Financing; Access; Happiness; Health Policy; Latin America; Caribbean